(untitled) (Research, Society and Development, 2025)
Orthodontics has evolved over the years, seeking faster, more effective and aesthetic treatments, with clear aligners gaining popularity due to their discretion and comfort. The manufacturing process for aligners can be done by direct 3D printing or thermoforming, with both methods having advantages and disadvantages. Thermoforming involves heating a thermoplastic material over a model to create the aligner. This process can modify the mechanical properties of the material, such as thickness and strength, influencing the effectiveness of orthodontic treatment. Direct 3D printing uses digital data to create the aligners layer by layer, without the need for molds, which results in greater dimensional accuracy and stability of mechanical properties, such as strength and rigidity. This review aims to compare the mechanical properties of printed orthodontic aligners with thermoformed aligners. Studies show that 3D printed aligners have better fit accuracy and greater resistance to deformation when compared to thermoformed ones, in addition to not undergoing significant changes due to heat. However, more studies are still needed to fully evaluate the effectiveness and biocompatibility of this technology. In conclusion, direct 3D printing stands out as an evolution in the manufacture of orthodontic aligners, providing more precise and effective results, although more research is needed to consolidate its clinical use.